Magnetic Resonance Imaging Exploration of the Human Brain During 10 kHz Spinal Cord Stimulation for Failed Back Surgery Syndrome: A Resting State Functional Magnetic Resonance Imaging Study. Issue 1 (11th April 2019) - De Groote, Sander; Goudman, Lisa; Peeters, Ronald; Linderoth, Bengt; Vanschuerbeek, Peter; Sunaert, Stefan; De Jaeger, Mats; De Smedt, Ann; Moens, Maarten
Abstract : Introduction: Apart from the clinical efficacy of high frequency spinal cord stimulation at 10 kHz, the underlying mechanism of action remains unclear. In parallel with spinal or segmental theories, supraspinal hypotheses have been recently proposed. In order to unveil hidden altered brain connectome patterns, a resting state functional magnetic resonance imaging (rsfMRI) protocol was performed in subjects routinely treated for back and/or leg pain with high‐frequency spinal cord stimulation (HF‐SCS) HF‐SCS at 10 kHz. Methods: RsfMRI imaging was obtained from ten patients with failed back surgery syndrome who were eligible for HF‐SCS at 10 kHz. Specifically‐chosen regions of interest with different connectivity networks have been investigated over time. Baseline measurements were compared with measurements after 1 month and 3 months of HF‐SCS at 10 kHz. Additionally, clinical parameters on pain intensity, central sensitization, pain catastrophizing, and sleep quality were correlated with the functional connectivity strengths. Results: The study results demonstrate an increased connectivity over time between the anterior insula (affective salience network) and regions of the frontoparietal network and the central executive network. After 3 months of HF‐SCS, the increased strength in functional connectivity between the left dorsolateral prefrontal cortex and the right anterior insula was significantly correlated with the minimum clinically important difference (MCID) value of the Pittsburgh sleep quality index. Conclusion: These findings support the hypothesis that HF‐SCS at 10 kHz might influence the salience network and therefore also the emotional awareness of pain.